2019
DOI: 10.3390/ma12071133
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Thymol in Poly(lactide-co-glycolide) (PLGA): Physical and Antibacterial Properties

Abstract: Thymol has been shown to be a safe and effective broad-spectrum antimicrobial agent that can be used as a food preservative. However, its volatile characteristics and strong odor limit its use in food products. The microencapsulation of this essential oil in biopolymers could overcome these disadvantages. In this work, thymol-loaded poly(lactide-co-glycolide) (PLGA) microparticles were successfully prepared and the optimal encapsulation efficiency was obtained at 20% (w/w) thymol. Microparticles containing thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 27 publications
5
32
0
Order By: Relevance
“…Zhun et al, prepared thymol-loaded PLGA MPs with an initial fast release followed by a slow and sustained release. These MPs demonstrated to have astrong antibacterial activity against Escherichia coli and Staphylococcus aureus confirmed by analytical tests in milk samples (Zhu et al 2019 ). These results showed that thymol-loaded PLGA MPs could be used as antimicrobial and preservation additives in food industry (Zhu et al 2019 ).…”
Section: Drug Encapsulation and In Vitro And In Vivo Releasementioning
confidence: 91%
See 3 more Smart Citations
“…Zhun et al, prepared thymol-loaded PLGA MPs with an initial fast release followed by a slow and sustained release. These MPs demonstrated to have astrong antibacterial activity against Escherichia coli and Staphylococcus aureus confirmed by analytical tests in milk samples (Zhu et al 2019 ). These results showed that thymol-loaded PLGA MPs could be used as antimicrobial and preservation additives in food industry (Zhu et al 2019 ).…”
Section: Drug Encapsulation and In Vitro And In Vivo Releasementioning
confidence: 91%
“…These MPs demonstrated to have astrong antibacterial activity against Escherichia coli and Staphylococcus aureus confirmed by analytical tests in milk samples (Zhu et al 2019). These results showed that thymol-loaded PLGA MPs could be used as antimicrobial and preservation additives in food industry (Zhu et al 2019). Same molecules with a high water solubility such as gentamicin sulfate can be encapsulated by post-loading procedure by simply putting PLGA MPs into drug solutions.…”
Section: Drug Encapsulation and Its Loading Efficiency Evaluationmentioning
confidence: 93%
See 2 more Smart Citations
“…Microspheres used in clinic include biodegradable and non-biodegradable materials [11,12]. Currently, biodegradable microspheres [13,14], such as polylactide (PLA) [15], have received wide attention.…”
Section: Introductionmentioning
confidence: 99%